Bottom Trawling Threatens Future Climate Refugia of Rhodoliths Globally - Fragkopoulou, Eliza; Serrão, Ester A.; Horta, Paulo A.; Koerich, Gabrielle; Assis, Jorge (Frontiers in Marine Science, 2021)
Climate driven range shifts are driving the redistribution of marine species and threatening the functioning and stability of marine ecosystems. For species that are the structural basis of marine ecosystems, such effects can be magnified into drastic loss of ecosystem functioning and resilience. Rhodoliths are unattached calcareous red algae that provide key complex three-dimensional habitats for highly diverse biological communities. These globally distributed biodiversity hotspots are increasingly threatened by ongoing environmental changes, mainly ocean acidification and warming, with wide negative impacts anticipated in the years to come. These are superimposed upon major local stressors caused by direct destructive impacts, such as bottom trawling, which act synergistically in the deterioration of the rhodolith ecosystem health and function. Anticipating the potential impacts of future environmental changes on the rhodolith biome may inform timely mitigation strategies integrating local effects of bottom trawling over vulnerable areas at global scales. This study aimed to identify future climate refugia, as regions where persistence is predicted under contrasting climate scenarios, and to analyse their trawling threat levels. This was approached by developing species distribution models with ecologically relevant environmental predictors, combined with the development of a global bottom trawling intensity index to identify heavily fished regions overlaying rhodoliths. Our results revealed the importance of light, thermal stress and pH driving the global distribution of rhodoliths. Future projections showed poleward expansions and contractions of suitable habitats at lower latitudes, structuring cryptic depth refugia, particularly evident under the more severe warming scenario RCP 8.5. Our results suggest that if management and conservation measures are not taken, bottom trawling may directly threaten the persistence of key rhodolith refugia. Since rhodoliths have slow growth rates, high sensitivity and ecological importance, understanding how their current and future distribution might be susceptible to bottom trawling pressure, may contribute to determine the fate of both the species and their associated communities.